Incorporating informal workers into twenty-first century social contracts - Rina Agarwala (United Nations Research Institute for Social Development (UNRISD), 2018)
This paper draws from an ongoing cross-national comparative project of informal workers' movements across eight countries of the global North and South to offer an initial framework of contemporary trends in informal workers' movements. Our findings suggest that present-day informal workers are mobilizing populations that were often excluded from 20th century labor movements. Such populations include workers operating within non-standard employment relationships (such as contract-based construction workers and garment workers, as well as self-employed domestic workers, transport workers, and trash collectors), within non-standard workspaces (including the street, private homes, and unregistered worksheds), and socially vulnerable groups (such as women, ethnic and racial minorities, and immigrants). By mobilizing these groups along class and social identity lines, informal workers are fighting to expand the definitions of "workers" and "employers" to include a larger and more diverse range of people, relationships, and occupations.
Keywords: 330